Sigma Virus (DMelSV) Incidence in Lines of Drosophila melanogaster Selected for Survival following Infection with Bacillus cereus - Meghan L. Bentz; Eve A. Humphrey; Lawrence G. Harshman; Marta L. Wayne (Psyche: A Journal of Entomology)
The immune response of Drosophila melanogaster is complex and involves both specific and general responses to parasites. In this study we tested for cross-immunity for bacteria and viruses by scoring the incidence of infection with the vertically transmitted Sigma virus (DMelSV) in the progeny of a cross between females transmitting DMelSV at high frequencies and males from lines subjected to three selection regimes related to resistance to Bacillus cereus. There was no significant difference in transmission of DMelSV among selection regimes, though results suggest that the B. cereus selected lines had lower rates of infection by DMelSV. We found a significant difference in viral infection with respect to the sex of the progeny, with males consistently less likely to be infected than females. Given a finite energy budget, flies that have experienced immune system challenge may show alterations in other life history traits. Later eclosing progeny were also less likely to be infected than earlier eclosing progeny, indicating a relationship with development time. Finally, there was a significant interaction between the timing of collection and the sex of the progeny, such that later eclosing males were the most resistant group. Increased development time is sometimes associated with increased energy acquisition; from this perspective, increased development time may be associated with acquiring sufficient resources for effective resistance.